Direct healthcare costs associated with management of asthma: comparison of two treatment regimens in Indonesia, Thailand and Vietnam. (3rd June 2022) - Aggarwal, Bhumika; Jones, Paul W.; Yunus, Faisal; Lan, Le Thi Tuyet; Boonsawat, Watchara; Ismaila, Afisi; Ascioglu, Sibel
Abstract: Objective: Daily inhaled corticosteroid (ICS) and long-acting beta-2-agonist (LABA) combinations comprising either regular maintenance therapy with ICS/LABA plus as-needed short-acting beta-2-agonist (SABA) or ICS-formoterol combinations used as maintenance and reliever therapy (MART) are recommended for moderate asthma. This analysis compares the direct costs of twice-daily fluticasone propionate/salmeterol (FP/salm) and budesonide/formoterol MART in three Southeast Asian countries. Methods: A literature review identified three randomized trials in patients with asthma (≥ 12 years) comparing regular twice-daily FP/salm with as-needed SABA versus MART in moderate asthma: AHEAD (NCT00242775/17 countries/2309 patients), COMPASS (AstraZeneca study SD-039-0735/16 countries/3335 patients), and COSMOS (AstraZeneca study SD-039-0691/16 countries/2143 patients). Economic analyses, conducted from a healthcare sector perspective (medication costs + healthcare utilization costs), applied unit costs from countries where healthcare costs are publicly available: Indonesia, Thailand and Vietnam. Results are expressed in British pound sterling (GBP/patient/year). Results: Annual exacerbation rates were low and differences between treatment strategies were small (range, FP/salm: 0.31–0.38, MART: 0.24–0.25) although statistically significant in favor of MART. Total average (minimum-maximum) direct costs (in GBP/patient/year) across the three studies were £187 (£137–£284), £158 (£125–£190), and £151 (£141–£164) for those who used FP/salm, and £242 (£217–£267), £284 (£237–£340) and £266 (£224–£315) for MART in Indonesia, Thailand and Vietnam, respectively. On average, total direct costs/patient/year with FP/salm were 22.8%, 44.6% and 43.0% lower than with MART for Indonesia, Thailand and Vietnam, respectively. Conclusions: In the three countries evaluated, total treatment costs with regular twice-daily FP/salm were consistently lower than with budesonide/formoterol MART due to lower direct healthcare costs.